Efficacy of anti-PD-1 monotherapy for recurrent or metastatic olfactory neuroblastoma - Hoshi, Yuta; Enokida, Tomohiro; Tamura, Shingo; Nakashima, Torahiko; Okano, Susumu; Fujisawa, Takao; Sato, Masanobu; Wada, Akihisa; Tanaka, Hideki; Takeshita, Naohiro; Tanaka, Nobukazu; Onaga, Ryutaro; et al. (Frontiers in Oncology, 2024)
Background: Olfactory neuroblastoma (ONB) is a rare malignant tumor of the head and neck. Due to its rarity, standard systemic therapy for this condition has yet to be established. In particular, the use of immune checkpoint inhibitors (ICIs) for the recurrent or metastatic (R/M) ONB population remains unclear. Methods: We retrospectively evaluated 11 patients with R/M ONB who received any systemic chemotherapy at two Japanese institutions (National Cancer Center Hospital East and Kyushu Medical Center) between January 2002 and March 2022 and analyzed outcomes by use of anti-PD-1 antibody (nivolumab or pembrolizumab) monotherapy. Results: Of the 11 patients, 6 received ICI (ICI-containing treatment group) and the remaining 5 were treated with systemic therapy but not including ICI (ICI-non-containing treatment group). Overall survival (OS) was significantly longer in the ICI-containing group (median OS: not reached vs. 6.4 months, log-rank p-value: 0.035). The fraction of ICI systemic therapy in the entire treatment period of this group reached 85.9%. Four patients (66.7%) in the ICI-containing treatment group experienced immune-related adverse events (irAE), with grades of 1/2. No irAE of grade 3 or more was seen, and no patient required interruption or discontinuation of treatment due to toxicity. Conclusion: ICI monotherapy appears to be effective and to contribute to prolonged survival in R/M ONB.